Design Optimization of Machining Parameters for AWJ Turning Operations of 718 Inconel Super alloy Based on the Taguchi - Kartal, Fuat (Uluslararasi Muhendislik Arastirma ve Gelistirme Dergisi, 2018)
Inconel Alloy 718 super alloy was machined usingabrasive water jet (AWJ) in this study. and nbsp;Following the cutting process, average surface roughness (Ra µm) andmaterial removal rate (MRR) were investigated and operating parameters wereoptimized using Taguchi method. Among the machining parameters were pumppressure (PP) (200, 350 MPa), nozzle feed rate (NFR) (5, 105 and 205 mm/min);abrasive flow rate (AFR) (50, 200 and 350 g/min); spindle speed (SS) (25, 50and 75 RPM) and standoff distance (SOD) (2, 8 and 14 mm). and nbsp; Taguchi L18 (21 x34) orthogonal factorialexperiment organization is adopted as experiment design. The effect ofparameters on Ra and depth of cut (DoC) was investigated statistically usingthe outcomes of the variance analysis and S/N rates. and nbsp; As a result of the empirical studies, PPproved to have the highest effect on Ra by 42.35%. On the other hand, NFRproved to have the highest effect on DoC by 72.85%. Increasing SS has improvedRa value while increasing DoC.
Keywords: Material Removal Rate; Inconel; Taguchi; Surface Roughness and Water Jet Turning; Taguchi; Surface Roughness and Water Jet Turning; Material Removal Rate; Inconel